Improving The Potential of Sentul Village as a Tourism Destination through Waste Management - L. Prima; F. Amalia; T. Lussetyowati; A. Ulfa; C. P. Putri; N. A. Zahra; S. R. Sadhiqa; Z. A. Putra (Archvisual: Jurnal Arsitektur dan Perencanaan, 2025)
Local tourism in rural areas, including Sentul Village, South Sumatra, is important in sustainable development. However, one of the challenges for the community in Sentul Village is ineffective waste management. This study examines how to handle waste effectively to support the potential of Sentul Village as a tourist destination. This research method is descriptive qualitative with a rationalistic approach. The results of the study indicate that poor waste management has affected the tourist attraction of Sentul Village. Thus, the development of tourism potential through waste management can be an example of the integration of local rural development.